Modelling the growth of Shorea robusta using growth ring measurements - Sapkota, P; Meilby, H (Banko Janakari, 2010)
This paper presents distance-independent diameter growth models for Sal (Shorea robusta Gaertn. f.) in Kankali Community Forest, Chainpur VDC, Chitwan. As the basis for modelling, stem discs were cut 0.3 m above-ground for a sample of 80 trees that had recently been felled. Growth rings were measured along four radii and, except for the outer part of a few discs originating from old trees, individual growth rings could be distinguished without major difficulty. Supplementary data were gathered as a basis for preparing models relating [i] diameter under bark to diameter on bark and [ii] diameter 0.3 m above-ground to diameter 1.3 m above-ground. Based on these data, auxiliary models were developed and used to convert growth ring measurements into diameter increment at breast height. The mean diameter increment was 0.87 cm/year (n = 1514) and the standard deviation was 0.33 cm/year. The relationships between diameter increment and current diameter, stem age, growth in previous years, rainfall and temperature were modelled. Four different models were presented. Rainfall during the growth season, particularly the months of May-July, proved to influence growth considerably and suggests a scope for dendroclimatological studies in Sal. Key words: Climate change; community forestry; diameter growth models; effect of rainfall; growth ring measurements DOI: 10.3126/banko.v19i2.2982 Banko Janakari, Vol. 19, No.2 2009 pp.25-32